PERWUJUDAN GAGASAN “COMPLEXITY AND CONTRADICTION IN ARCHITECTURE” OLEH ROBERT VENTURI PADA ARSITEKTUR PURI AGUNG KARANGASEM BALI - Beatrix Hendrata, Ilona; Saliya, Yuswadi (Jurnal Riset Arsitektur, 2023)
Abstract - Postmodern architecture was initiated around the 1960s, when architects who were supported by the ideas of philosophers and writers saw that modern architecture was no longer in accordance with the times because of the inability to answer the specific cultural context in an architectural work. A character named Robert Venturi is one who plays an important role in the development of Postmodern Architecture with various ideas, the most famous of which is "Less is Bore" which responds to the architectural motto "Less is More" in Modern architecture. Robert Venturi wrote several books, including "Complexity and Contradiction in Architecture" which contains Robert Venturi's Postmodern ideas. Postmodern architecture which has eclectic and hybrid thinking is also developing rapidly in Indonesia, especially on the island of Bali as one of the cultural centers. The architecture that characterizes the island of Bali is the temple as a place of worship and the castle as the residence of the Balinese kingdom. Puri Agung Karangasem is located in the center of Amlapura City, a kingdom in East Bali. It was founded at the end of the 19th century by Anak Agung Anglurah Ktut Karangasem who was appointed as Stadholder II. Puri Agung Karangasem applies the concept of a blend of several cultures in its architecture. Balinese architecture, colonial architecture according to the development period, and there is Chinese influence. This research is qualitative with descriptive-analytical approach. The data that has been collected will be processed by comparing, grouping and summarizing. The study will look for Venturi's ideas in "Complexity and Contradiction in Architecture" which are reflected in the architecture of Puri Agung Karangasem. The results of the study show that many of Venturi's ideas are realized in terms of mass and spatial planning, building figures and ornamentation resulting from acculturation of the three cultures. This proves that before Postmodern Architecture developed in 1960 and Venturi issued the idea, Puri Agung Karangasem on the island of Bali had implemented this concept in the construction of the Puri since more than 60 years earlier. Keyword: Castle, Bali, Robert Venturi, Postmodern Architecture